How Der Sklavenkrieg became The Gladiators: Reflections on Edith Simon’s translation of Arthur Koestler’s novel - MacAdam, Henry Innes (International Journal of English Studies, 2017)
All German original manuscripts of Arthur Koestler’s first two novels (The Gladiators and Darkness at noon) were lost during World War II. A MS of each was recently recovered, allowing for the first time a comparison with their initial English translations, for almost 80 years the basis of all other translations. Both novels will be published in German and in a new English translation that allows comparison with the original English editions. This article provides context for the first translation of Der Sklavenkrieg by Edith Simon (1917–2003), through correspondence with Simon’s younger sister Inge Simon Goodwin (1923–2014), and Simon’s daughter, Antonia Reeve. It also briefly addresses some editorial changes in the table of contents for The Gladiators, anomalies within Simon’s rendition of descriptive prose, and an example of Simon’s skills as translator of Koestler’s imaginative prose. These are preliminary observations only, in anticipation of the novel’s retranslation and republication in 2018.